2000 IEEE International Reliability Physics Symposium Proceedings. 38th Annual (Cat. No.00CH37059)
DOI: 10.1109/relphy.2000.843891
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for recombination at oxide defects and new SILC model

Abstract: This work presents experimental and computational investigations on the physical mechanisms of SILC. Carrier separation measurements are carried out on MOS samples with oxide thickness 6 -8 nm, highlighting the electron and hole contributions to the SILC. We have investigated the relation between these components by means of timerelaxation. It is found that a linear relationship holds between electron SILC and hole SILC, measured at different times after the initial high-field stress. The same linearity has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
2
2
0
Order By: Relevance
“…of gate electrons tunneling into bulk-oxide traps (mechanism 1 in figure 11) and the recombination of these electrons with substrate holes (mechanism 2 in figure 11). The number of substrate holes, which is temperature dependent, controls the INE mechanism, and we have shown that the gate current is temperature dependent in the voltage range 0 to −1 V. This interpretation is in agreement with the model originally proposed by Ielmini et al [3,4,28,29].…”
Section: Neutral Tat and Lvsilcsupporting
confidence: 92%
“…of gate electrons tunneling into bulk-oxide traps (mechanism 1 in figure 11) and the recombination of these electrons with substrate holes (mechanism 2 in figure 11). The number of substrate holes, which is temperature dependent, controls the INE mechanism, and we have shown that the gate current is temperature dependent in the voltage range 0 to −1 V. This interpretation is in agreement with the model originally proposed by Ielmini et al [3,4,28,29].…”
Section: Neutral Tat and Lvsilcsupporting
confidence: 92%
“…Secondly, the TAT inelastic current is given by the equilibrium of gate electrons tunneling into bulk-oxide traps (mechanism 1 in figure 11) and the recombination of these electrons with substrate holes (mechanism 2 in figure 11). The number of substrate holes, which is temperature dependent, controls the INE mechanism, and we have shown that the gate current is temperature dependent in the voltage range 0 to −1 V. This interpretation is in agreement with the model originally proposed by Ielmini et al [3,4,28,29].…”
Section: Neutral Tat and Lvsilcsupporting
confidence: 92%
“…Reliability issues include several different mechanisms of charge loss and fluctuation, such as Stress-Induced Leakage Current (SILC) through the tunnel oxide [5,6], charge trapping in the dielectrics after cycling, charge de-trapping from the tunnel oxide [7], Random Telegraph Noise (RTN) [8], high temperature charge loss and charge sharing between cell through the inter-poly dielectric [9]. Word Line (WL) -substrate short and fast erase bit impact device reliability short term and are usually screened at wafer sorting.…”
Section: Cell Structure and Operationmentioning
confidence: 99%